Electrode material for high power density secondary battery and high power density secondary battery using the same

A highly crystalline multilayer metal-organic structure enables high-density electrochemical insertion of anions and cations, addressing the limitations of existing secondary batteries and enhancing energy density.

JP7599733B2Active Publication Date: 2024-12-16NAT INST FOR MATERIALS SCI
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
JP2023037899
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2023-03-10
Publication Date
2024-12-16
Estimated Expiration
2038-03-02

AI Technical Summary

Technical Problem

Existing secondary batteries based on a rocking chair mechanism lack materials that can effectively electrochemically insert both anions and cations as charge carriers, limiting their energy density and performance improvements.

Method used

A highly crystalline multilayer metal-organic structure with specific X-ray diffraction peak characteristics is developed, allowing for the electrochemical insertion of both anions and cations at high density, characterized by a full width at half maximum of the X-ray diffraction peak from the (100) plane of 1.0° (2θ) or less.

Benefits of technology

This structure significantly enhances energy density in secondary batteries by enabling both anions and cations to function as charge carriers, surpassing conventional technologies in performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007599733000001
    Figure 0007599733000001
  • Figure 0007599733000002
    Figure 0007599733000002
  • Figure 0007599733000003
    Figure 0007599733000003
Patent Text Reader

Abstract

A material is provided that is suitable as an electrode material for secondary batteries based on a rocking chair mechanism, and that is capable of electrically intercalating both anions and cations at a high density. The present invention provides an electrode material for a secondary battery, which comprises a multilayer metal-organic framework and is capable of electrochemically inserting at least one type of cation and at least one type of anion, wherein the full width at half maximum of an X-ray diffraction peak from the (100) plane of the multilayer metal-organic framework measured using CuKα radiation is 1.0° (2θ) or less.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to an electrode material for a high power density secondary battery and a high power density secondary battery using the same, and more specifically, to an electrode material for a secondary battery capable of absorbing and releasing charge carriers at high density, and a secondary battery that achieves high power density by using the secondary battery electrode material. [Background technology]

[0002] Secondary batteries based on a rocking chair mechanism, such as lithium-ion secondary batteries, have excellent properties such as high capacity, high power density, and virtually no memory effect, and therefore have been used or proposed for use in a wide range of applications, such as various electric and electronic devices such as mobile devices, various transport machines such as electric vehicles, etc. In recent years, with the expansion of these applications and the improvement of performance, there has been a demand for even higher capacity, higher power density, and higher stability during repeated use. In secondary batteries based on this rocking chair mechanism, layered oxides or polyanion-based materials are basically used as the positive electrode, and graphite is mainly used as the negative electrode. In order to meet the above requirements, various electrode materials and operating principles have been proposed in recent years with the aim of improving the energy density. In the conventional secondary battery, Li + The mainstream is to use cations such as F as charge carriers and pass electrons to an external circuit. -Also proposed are those using anions as charge carriers such as those described above (see, for example, Patent Document 1). In addition, a new operating principle of a secondary battery has been proposed in which both anions and cations are used as charge carriers to pass electrons to an external circuit, thereby improving the energy density (see, for example, Patent Document 2 and Patent Document 3). However, there have not been many material systems to which the operating principle of using anions as charge carriers or the operating principle of using both anions and cations as charge carriers can be applied, and therefore the characteristics of the secondary batteries proposed using electron carriers other than these cations have not been substantially improved compared to conventional secondary batteries. For example, the battery voltage of the secondary battery prepared in Patent Document 2 was not necessarily sufficiently high. In addition, Patent Document 3 does not describe the battery characteristics themselves, such as the capacity of the prepared secondary battery, and it has not been confirmed that a practical electrode material has been obtained. Meanwhile, in recent years, various sheet-like compounds with high electronic conductivity have been synthesized. Among them, structures have been reported that not only have high electronic conductivity, but are stable in aqueous electrolytes and many organic electrolytes and active in redox reactions (see, for example, Non-Patent Document 1). However, although electric double layer capacitors have been proposed as applications of these structures, their practical applicability as electrode materials for secondary batteries has not been clear. In particular, it has not been clear whether cations and / or anions, which are necessary for use as secondary batteries based on a rocking chair mechanism, can be electrochemically inserted, and the type and degree of the insertable cations and / or anions, and also a structure suitable for electrochemical insertion of cations and / or anions has not been clear. [Prior art documents] [Patent documents]

[0003] [Patent Document 1] JP 2013-145758 A [Patent Document 2] International Publication No. 2013 / 107798 [Patent Document 3] JP 2016-103407 A [Non-patent literature]

[0004] [Non-Patent Document 1] Nature Materials,16(2),220-224(2017) Summary of the Invention [Problem to be solved by the invention]

[0005] In view of the above background art, an object of the present invention is to provide a material that is suitable as an electrode material for a secondary battery based on a rocking chair mechanism, and that is capable of electrically inserting both anions and cations at a high density. A further object of the present invention is to provide a secondary battery using the above-mentioned electrode material, in which both anions and cations are used as charge carriers that pass electrons to an external circuit, thereby achieving a remarkably improved energy density as compared with that of the prior art. [Means for solving the problem]

[0006] As a result of intensive research aimed at solving the above problems, the present inventors have found that an electrode material for a secondary battery, which has a multilayer metal-organic framework and high crystallinity characterized by a full width at half maximum of an X-ray diffraction peak of a predetermined value or less, can electrically insert both anions and cations suitable as charge carriers in a secondary battery, and that the above problems can be effectively solved by utilizing this, thereby completing the present invention. That is, the present invention provides: [1] The electrode material for a secondary battery comprises a multilayer metal-organic framework and is capable of electrochemically inserting at least one type of cation and at least one type of anion, wherein the full width at half maximum of an X-ray diffraction peak from a (100) plane of the multilayer metal-organic framework is 1.0° (2θ) or less, as measured using CuKα radiation.

[0007] Moreover, the following [2] to

[17] are each a preferred embodiment or aspect of the present invention. [2] The electrode material for a secondary battery according to [1], wherein the multilayer metal-organic framework has an average pore diameter of 0.5 to 3.0 nm as measured by observation with a transmission electron microscope. [3] The electrode material for a secondary battery according to [1] or [2], which is used for a positive electrode. [4] 3. An electrode material for a secondary battery according to claim 1, which is used for a negative electrode. [5] Electrical conductivity is 10 -6 Scm -1 The electrode material for a secondary battery according to any one of [1] to [4] above. [6] The at least one cation is Li + , Na + , Mg 2+ , Ca 2+ , or Al 3+ The electrode material for a secondary battery according to any one of [1] to [5], [7] The at least one anion is TFSI - , P.F. 6 - , ClO 4 - , F - , or Cl - The electrode material for a secondary battery according to any one of [1] to [6], [8] The electrode material for a secondary battery according to any one of [1] to [7], wherein the metal-organic framework has at least one 3d transition element as a metal of a complex moiety. [9] The electrode material for a secondary battery according to any one of [1] to [8], wherein the metal-organic framework has a ligand containing at least one element selected from nitrogen, boron, oxygen, fluorine, and sulfur.

[10] The electrode material for a secondary battery according to any one of [1] to [9], which is stable in an organic electrolyte solution and an aqueous electrolyte solution.

[11] The electrode material for a secondary battery according to any one of [1] to

[10] , further comprising an auxiliary electrochemical agent and a binder.

[12] A secondary battery comprising a positive electrode, a negative electrode, and an electrolyte, the positive electrode and negative electrode using the electrode material for a secondary battery according to any one of [1] to

[11] .

[13] A secondary battery comprising a negative electrode using the electrode material for a secondary battery according to any one of [1] to

[11] , a positive electrode, and an electrolyte.

[14] The secondary battery according to

[12] or

[13] , wherein the at least one type of cation and the at least one type of anion both function as charge carriers.

[15] The secondary battery according to any one of

[12] to

[14] , wherein the electrolytic solution is an organic electrolytic solution.

[16] The secondary battery according to any one of

[12] to

[14] , wherein the electrolytic solution is an aqueous electrolytic solution.

[17]

[11] An electric / electronic device, or a transport machine, comprising the secondary battery according to any one of

[11] to

[16] . Effect of the Invention

[0008] According to the present invention, there is provided an electrode material which is capable of electrically intercalating both anions and cations suitable as charge carriers in secondary batteries at a practically sufficient level of high density and is suitable for use in electrodes of secondary batteries based on a rocking chair mechanism. A secondary battery using the electrode material of the present invention has an energy density that is remarkably improved compared to conventional techniques, and can make a significant contribution to the currently strong demand for high performance secondary batteries. [Brief description of the drawings]

[0009] [Figure 1] 4 shows the results of a charge / discharge test of the secondary battery produced in Example 1. [Diagram 2] 1 is a powder X-ray diffraction pattern of the secondary battery electrode material used in Example 1. [Diagram 3] 3A and 3B are transmission electron microscope images of the electrode material for a secondary battery used in Example 1, where FIG. 3A is an image observed at a magnification of 400,000 times, and FIG. 3B is an image observed at a magnification of 1,000,000 times. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0010] The present invention relates to an electrode material for a secondary battery, which comprises a multilayer metal-organic framework and is capable of electrochemically inserting both at least one type of cation and at least one type of anion, wherein the full width at half maximum of an X-ray diffraction peak from a (100) plane of the multilayer metal-organic framework is 1.0° (2θ) or less, as measured using CuKα radiation. The electrode of the present invention is an electrode material comprising a metal-organic framework in which a metal and an organic substance are combined. Therefore, by changing the combination of the metal portion and the organic portion, particularly the ligand portion, the electrochemical characteristics can be adjusted relatively freely. Therefore, a desired electrode can be designed and manufactured with a relatively high degree of freedom in accordance with the characteristics and performance of the desired secondary battery and the functions and physical properties of the electrode to realize them. In addition, since the metal-organic framework contains multiple layers and has high crystallinity characterized by a full width at half maximum of an X-ray diffraction peak that is equal to or less than a predetermined value, that is, since the multiple layers of the metal-organic framework have a bulk structure in which they are stacked densely and regularly to such an extent that they exhibit high crystallinity, anions and cations, which are charge carriers, can be electrochemically inserted between the layers at a high density. Therefore, when the metal-organic framework is used as an electrode material for a secondary battery, a secondary battery having an energy density that is remarkably improved compared to conventional techniques can be realized.

[0011] (metal-organic structure) The metal-organic framework constituting the electrode material for a secondary battery of the present invention is a concept widely known in the technical field, and in the present invention, any metal-organic framework can be used as long as it falls within the scope of the concept. The metal-organic framework preferably used in the present invention has a periodic structure including a metal portion composed of at least one type of metal and an organic portion including a ligand coordinated to the at least one type of metal, and the metal portion and the organic portion are periodically repeated.

[0012] The metal-organic framework preferably used in the present invention may have a two-dimensional periodic structure or a one-dimensional or three-dimensional periodic structure due to the coordination structure between the metal portion and the organic portion, but is particularly preferably a so-called two-dimensional metal complex having a two-dimensional periodic structure. In this case, the metal-organic framework having a two-dimensional periodic structure forms a sheet-like structure in which substantially all of the ligands and the metal portion are present on approximately the same plane, and the sheet-like metal-organic framework forms a bulk structure in which the layers are densely and regularly stacked to such an extent that the structure exhibits high crystallinity, thereby forming a bulk structure in which anions and cations can be electrochemically inserted between layers at a high density. The high crystallinity of the bulk structure is characterized by the full width at half maximum of the X-ray diffraction peak being equal to or less than a predetermined value, and more specifically, is specified by the full width at half maximum of the X-ray diffraction peak from the (100) plane of the multilayer metal-organic framework being equal to or less than 1.0° (2θ) as measured using CuKα radiation. The full width at half maximum of the X-ray diffraction peak from the (100) plane of the multilayer metal-organic framework is preferably equal to or less than 0.7° (2θ), and more preferably equal to or less than 0.5° (2θ).

[0013] The multi-layered metal-organic framework preferably has an average pore diameter of 0.5 to 3.0 nm. When the multi-layered metal-organic framework has an average pore diameter in the above range, anions and cations can be occluded and released between the layers at a higher density. The average pore diameter of the multi-layer metal-organic framework is more preferably from 1 to 2 nm, and particularly preferably from 1.3 to 1.7 nm. The average pore diameter of the multilayer metal-organic framework can be measured by observation with a transmission electron microscope. More specifically, the average pore diameter can be determined by observing an image of the multilayer metal-organic framework obtained by a transmission electron microscope, and more specifically, the average pore diameter can be determined by averaging the diameters of 10 or more bright areas corresponding to pores in an image obtained by observation with a transmission electron microscope of the multilayer metal-organic framework. The average particle size of the multilayer metal-organic framework can also be measured by observation with a transmission electron microscope. More specifically, the average particle size can be determined by averaging the diameters of 20 or more particles of shapes corresponding to the particles of the multilayer metal-organic framework in an image obtained by observation with a transmission electron microscope of the multilayer metal-organic framework. The average particle size of the multi-layer metal-organic framework is preferably 10 to 300 nm, and more preferably 50 to 100 nm. When the average particle size of the multilayer metal-organic framework is within the above range, sufficient ion diffusion and high crystallinity can be achieved at an even higher level.

[0014] The average pore diameter of the metal-organic framework can also be measured by a nitrogen adsorption method. In addition, the average pore diameter of the metal-organic framework can be determined by measuring the relationship between the relative pressure and the amount of adsorption of nitrogen molecules in the metal-organic framework by a nitrogen adsorption method and calculating the pore diameter distribution from the pressure at which condensation occurs in the pores.

[0015] As an application utilizing the electrochemical properties of conventional metal-organic frameworks, for example, electric double layer capacitors have been proposed as described in Non-Patent Document 1, but the practical possibility of using them as electrodes for secondary batteries has not been confirmed. This is because the conventional technology focuses on the high specific surface area of ​​sheet-shaped metal-organic frameworks and assumes the utilization of their surface reactions. On the other hand, the reaction of a battery is basically a bulk reaction in which the inside of the solid also contributes to the reaction, and therefore a high energy density is obtained, so that sheet-shaped metal-organic frameworks have not been considered suitable as electrode materials. In the electrode material for secondary batteries of the present invention, a bulk structure is formed in which multiple sheet-like metal-organic frameworks are densely and regularly stacked to such an extent that the multiple layers exhibit high crystallinity, as characterized by a full width at half maximum of an X-ray diffraction peak not greater than a predetermined value. Surprisingly, it has been found that anions and cations suitable as charge carriers in secondary batteries can be electrochemically inserted between the layers at high density, and that by utilizing this as an electrode material, a high-density secondary battery can be manufactured in which both anions and cations are used as charge carriers. In order to realize an appropriate electrical conductivity as an electrode, the electrical conductivity of the layered metal-organic framework used in the present invention is 10 -2 Scm -1 It is preferable that the number of the electrodes is 10 or more. -1 ~10 3 Scm -1 More preferably, it is 10 2 ~10 3 Scm -1 It is particularly preferred that:

[0016] From the viewpoint of forming a highly crystalline bulk structure in which a plurality of sheet-like metal-organic frameworks are laminated, the metal-organic framework preferably has a two-dimensional periodic structure. However, the metal-organic framework may have a three-dimensional periodic structure as long as anions and cations can be electrochemically inserted therein. Furthermore, a sheet-like metal-organic framework having a two-dimensional periodic structure may partially have a three-dimensional structure.

[0017] (Metal in the complex) The metal-organic framework constituting the electrode material of the present invention preferably has at least one 3d transition element as the metal of the complex portion. By using a 3d transition element as the metal of the complex portion, it becomes easy to take a planar coordination structure as the coordination structure, and it becomes easy to form a sheet-shaped metal-organic framework in which the metal portion and the organic portion have a two-dimensional periodic structure. More specifically, it is preferable to use at least one metal selected from scandium, titanium, vanadium, chromium, manganese, iron, cobalt, nickel, copper, and zinc as the metal of the complex portion. Among these, it is particularly preferable to use copper or nickel. The type of metal in the complex portion may be appropriately selected depending on the desired electrical conductivity and the type of cation and / or anion to be electrochemically inserted. The metal in the complex portion may be of one type or a combination of two or more types through the metal-organic framework.

[0018] (ligand) The metal-organic framework constituting the electrode material of the present invention preferably has, as a ligand of the organic portion, a ligand containing at least one element selected from Group 13 (boron group), Group 14 (carbon group), Group 15 (nitrogen group), Group 16 (chalcogen), and Group 17 (halogen), and particularly preferably has a ligand containing at least one element selected from nitrogen, boron, oxygen, fluorine, and sulfur. It is also preferable to use a ligand having three or more bidentate coordination sites, at least one of which is NH. Here, "bidentate" means that the same ligand has two bonds that coordinate to the same metal nucleus. Also, "having three or more bidentate coordination sites" means that the same ligand has three or more pairs of "bidentate" groups.

[0019] The ligand preferably has an aryl group, and a particularly preferred ligand is Ar(NH) n X m-n Here, Ar represents an aryl group, and is particularly preferably a benzene ring. X is preferably at least one selected from the group consisting of O, S, Se and Te, more preferably O or S, and particularly preferably S. m is the number of bonds depending on the size and structure of the aryl group and is an integer of 6 or more, and n is an integer of 3 or more and m or less. Particularly preferably, the ligand is Bz(NH) n X 6一n It is preferable that the compound is represented by the following formula: Here, Bz represents a benzene ring, and X and n have the same definitions as above, and n is preferably 3 or 6, and more preferably 6. A particularly preferred ligand is hexaaminobenzene. The ligand of the organic portion may be used alone or in combination of two or more kinds through the metal-organic framework.

[0020] (electrode material) The electrode material of the present invention may further contain a current promoter and a binder in addition to the multilayer metal-organic framework. By including the electrochemical promoter, the multiple layers of the metal-organic framework contained in the electrode material can be electrically bonded to each other, thereby imparting sufficient and uniform conductivity to the electrode material. Examples of the electric coagent include metals such as titanium, platinum, gold, silver, copper, aluminum, cobalt, iron, magnesium, nickel, and zinc; metal compounds such as titanium oxide, tin oxide, zinc oxide, gallium oxide, indium oxide, aluminum oxide, chromium oxide, cobalt oxide, copper oxide, iron oxide, titanium carbide, vanadium carbide, and tungsten carbide; and carbon materials such as carbon black, acetylene black, carbon nanotubes, carbon fibers, activated carbon, and graphite. Among these, it is preferable to use a carbon material, and it is particularly preferable to use acetylene black. The electrostatic coagent may be used alone or in combination of two or more kinds.

[0021] By using a binder, the mechanical strength of the electrode can be ensured, and a stable electrode can be formed. The binder is not particularly limited as long as it is a resin capable of binding each material.Specific examples include, but are not limited to, polytetrafluoroethylene (PTFE), polyethylene oxide (PEO), polyethylene glycol (PEG), polyvinylidene fluoride (PVDF), polyvinylidene fluoride-hexafluoropropylene copolymer (PVDF-HFP), carboxymethyl cellulose (CMC), styrene-butadiene rubber (SBR), polyacrylic acid (PAA), polyvinyl alcohol (PVA), polyvinyl butyral (PVB), polyacrylonitrile (PAN), polyimide (PI), etc. Among these, it is particularly preferable to use polyvinylidene fluoride. In the electrode material of the present invention, one type of binder may be used alone, or two or more types of binders may be used in combination. The binder may be used by diluting with a nitrogen-containing solvent such as N,N-dimethylformamide or N-methyl-2-pyrrolidone, an ester such as γ-butyrolactone, an ethylene glycol, an alcohol, a ketone, or a nitrile.

[0022] With respect to the total mass of the electrode material which contains the multi-layer metal-organic framework as an essential component and may or may not contain optional components such as a current enhancer and a binder, the content of the multi-layer metal-organic framework is, for example, preferably 10 to 90 mass%, more preferably 15 to 90 mass%, and further preferably 25 to 90 mass%. By making the content equal to or greater than the lower limit of the above range, the rated capacity of the secondary battery can be increased, while by making the content equal to or less than the upper limit of the above range, the mechanical strength of the electrode material can be increased by increasing the content of the binder, and the electrical conductivity and uniformity of the electrode material can be increased by increasing the content of the static eliminator.

[0023] The electrical conductivity of the electrode material for secondary batteries of the present invention is not particularly limited. -6 Scm -1 It is preferable that the number of the electrodes is 10 or more. -3 Scm -1 More preferably, 10-2 Scm -1 More preferably, it is equal to or greater than this. Electrical conductivity is 10 -6 Scm -1 Due to the above, the charge can be efficiently transported to the outside, and the material can be particularly suitably used as an electrode material for a secondary battery.

[0024] The method for producing the metal-organic framework used in the electrode material for a secondary battery of the present invention is not particularly limited, and various methods conventionally used for producing metal-organic frameworks, such as a solution method, a hydrothermal method, an electrochemical method, etc., can be appropriately used. From the viewpoint of efficiently producing a bulk multilayer metal-organic framework having high crystallinity, it is preferable to improve the crystallinity by controlling the crystal growth rate, and in particular, it is preferable to improve the crystal growth rate as compared with the conventional techniques. For example, when a metal-organic framework is produced by reacting a compound containing a complex metal with a compound having a ligand in a solvent, the crystal growth rate can be appropriately controlled by appropriately setting the type of solvent, the concentration of the compound containing a complex metal, and / or the concentration of the compound having a ligand. In order to improve the crystal growth rate, it is preferable to set the concentration of the compound containing a complex metal and / or the concentration of the compound having a ligand high, in comparison with the conventional technology. In addition, by using a relatively low-density solvent and precipitating the generated metal-organic framework particles in the solvent, the area of ​​the crystal growth site can be increased, and a high crystal growth rate can be achieved. As a relatively low-density solvent, for example, dimethyl sulfoxide can be preferably used, but is not limited thereto. It is particularly preferable to synthesize the metal-organic framework by a method such as that described in the examples of this application.

[0025] The electrode material for secondary batteries of the present invention can electrochemically insert cations and anions at a high density, and therefore can be suitably used as an electrode material for secondary batteries for both positive and negative electrodes. (positive electrode) The electrode material for a secondary battery of the present invention can be suitably used particularly as a positive electrode of the electrode material for a secondary battery, in which the highly crystalline multi-layer metal-organic framework constituting the electrode material for a secondary battery of the present invention can release cations contained in the electrolyte during charging and can occlude anions contained in the electrolyte during charging. In this case, the negative electrode, which is the counter electrode, may be made of the electrode material for a secondary battery of the present invention, or may be made of lithium metal or lithium iron phosphate (LiFePO 4 The negative electrode may be composed of other negative electrode materials such as lithium compounds such as ZnO, silicon, and tin.

[0026] (Negative electrode) The electrode material for a secondary battery of the present invention can also be suitably used as a negative electrode for the electrode material for a secondary battery. In this case, the highly crystalline multi-layer metal-organic framework constituting the electrode material for a secondary battery of the present invention can occlude cations contained in the electrolyte during charging and can release anions contained in the electrolyte during charging.

[0027] (electrolyte) The electrolyte used in combination with the positive electrode and / or negative electrode constituted by the electrode material of the present invention is not particularly limited as long as it contains at least one type of cation and at least one type of anion that can be electrochemically inserted into the highly crystalline multi-layered metal-organic framework that constitutes the electrode material of the present invention. In order to achieve a high energy density and a high operating voltage, the at least one cation is Li + , Na + , Mg 2+ , Ca 2+ , or Al 3+ Preferably, Li + It is particularly preferred that: In order to achieve a high energy density and a high operating voltage, the at least one anion is preferably TFSI - , P.F. 6 - , ClO 4 - , F - , or Cl- is preferably ClO 4 - , P.F. 6 - In the case of an aqueous electrolyte, it is particularly preferable that the anion is TFSI. - It is particularly preferred to use

[0028] The electrolyte used in combination with the positive electrode and / or negative electrode constituted by the electrode material of the present invention may be an aqueous electrolyte or an organic electrolyte. By using an aqueous electrolyte solution, it is possible to realize a high energy density, and thus a secondary battery with a high power density can be realized. The use of an organic electrolyte can improve stability. The highly crystalline multilayer metal-organic framework constituting the electrode material of the present invention can be designed to be stable in both organic and aqueous electrolytes, and can therefore be used with a high degree of freedom in secondary batteries of various configurations.

[0029] The solvent constituting the organic electrolyte solution is not particularly limited as long as it is a solvent in which the cations and anions can be dissolved and in which the secondary battery can function. For example, a known organic solvent used in a lithium ion secondary battery can be appropriately adjusted and used. Examples of the organic solvent include ethers such as triethylene glycol dimethyl ether and tetraethylene glycol dimethyl ether, cyclic carbonates such as ethylene carbonate, fluoroethylene carbonate, difluoroethylene carbonate, propylene carbonate, and butylene carbonate, and chain carbonates such as dimethyl carbonate, diethyl carbonate, and ethyl methyl carbonate. Furthermore, an ionic liquid may be used as the organic solvent. The organic solvent may be used alone or in combination of two or more. In the case of using two or more organic solvents in combination, it is particularly preferable to use a mixture of ethylene carbonate and diethyl carbonate.

[0030] (Secondary battery) A secondary battery, which is a preferred embodiment of the present invention, can be constructed by combining the above-mentioned positive electrode, negative electrode, and electrolyte. In the secondary battery which is a preferred embodiment of the present invention, both the anions and cations can be used as charge carriers that pass electrons to an external circuit, so that the energy density can be improved significantly compared to the prior art. The secondary battery, whose energy density has been remarkably improved compared to conventional techniques, has thus been made high performance and is particularly suitable for use in various electric and electronic devices such as mobile devices, and various transportation machines such as electric vehicles.

[0031] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to the following examples in any sense. EXAMPLES

[0032] [Example 1] (Synthesis of Metal-Organic Frameworks) 20 mg of copper nitrate 2.5 hydrate was added to 2 mL of degassed dimethyl sulfoxide, and a dimethyl sulfoxide solution containing 0.15 mM of hexaaminobenzene was added to the mixture. Three drops of 6 M ammonia hydroxide solution were added to the mixed solution to obtain a precipitate. The precipitate was washed with anhydrous THF (tetrahydrofuran) and dried in vacuum to obtain the desired metal-organic framework. These operations were carried out in a glove box. The metal-organic framework obtained above was observed by various methods such as powder X-ray diffraction (PXRD), X-ray photoelectron spectroscopy (XPS), and transmission electron microscopy (TEM), and was confirmed to be a layered metal complex with Cu as the metal core and hexaaminobenzene as the ligand. More specifically, detailed crystal structure analysis by synchrotron X-ray diffraction experiments confirmed that it was a layered substance. In addition, the full width at half maximum of the X-ray diffraction peak from the (100) plane of the layered metal complex measured using CuKα radiation was 0.5° (2θ), confirming that the layered metal complex was a bulk with high crystallinity.

[0033] The metal-organic framework obtained above was observed with a transmission electron microscope under the following conditions to measure the pore size and particle size of the metal-organic framework. Sample preparation: Approximately 5 mg of the metal-organic framework obtained above was added to ethanol and dispersed by ultrasonic waves. The dispersion was precipitated at 10,000 rpm using a centrifuge, and the supernatant was used as a sample for observation. Observation conditions: The prepared observation sample was dropped onto the observation grid of an atomic resolution TEM (transmission electron microscope), and observation was performed at an accelerating voltage of 80 kV. The resulting transmission electron microscope image is shown in FIG. The average particle size of the metal-organic framework obtained by analyzing the image of FIG. 3(a) was 49 nm, and the average pore size of the metal-organic framework obtained by analyzing the image of FIG. 3(b) was 1.31 nm.

[0034] (Preparation of electrodes for secondary batteries) The layered metal-organic framework prepared above was used as an active material, and was mixed with acetylene black as a charge coagent and polyvinylidene fluoride as a binder in a ratio of 7:2:1. The mixture was then applied onto aluminum foil to prepare an electrode for a secondary battery.

[0035] (Production and evaluation of secondary batteries) The organic electrolyte was a 7:3 mixture of ethylene carbonate and diethyl carbonate, and the electrolyte was lithium hexafluorophosphate (LiPF 6 A secondary battery was fabricated using a 1 mol / L solution of 1,000g ... The results of evaluating the charge / discharge characteristics of the secondary battery are shown in Figure 1. The capacity exceeded 200 mAh / g, achieving a high capacity characteristic that far surpasses that of conventional technology. Such a significant improvement in the specific capacity is believed to be due to the fact that both cations and anions function as charge carriers and that charge carriers are absorbed / desorbed at a high density. [Industrial Applicability]

[0036] The electrode material of the present invention is suitable for use in electrodes of secondary batteries based on a rocking chair mechanism, and secondary batteries using the electrode material have high practical value, for example, in that they have an energy density that is significantly improved compared to conventional technology. Therefore, these electrode materials and secondary batteries have high applicability in various industrial fields, such as various electric and electronic devices including mobile devices, and various transportation machines including electric vehicles, etc.

Claims

1. 1. An electrode material for a secondary battery, comprising a multi-layer metal-organic framework, capable of electrochemically intercalating both at least one cation and at least one anion, the metal-organic framework includes a metal portion composed of at least one type of metal and an organic portion including a ligand coordinated to the at least one type of metal, and has a periodic structure in which the metal portion and the organic portion are periodically repeated due to a coordination structure between the metal portion and the organic portion; the full width at half maximum of the X-ray diffraction peak from the (100) plane of the multilayer metal-organic framework measured using CuKα radiation is 1.0° (2θ) or less; The above electrode material for secondary batteries is stable against organic electrolyte solutions and aqueous electrolyte solutions.

2. 2. The electrode material for a secondary battery according to claim 1, wherein the multilayer metal-organic framework has an average pore size, which is an average size of bright areas in an image obtained by observation with a transmission electron microscope, of 0.5 to 3.0 nm.

3. The electrode material for a secondary battery according to claim 1 or 2, which is used for a positive electrode.

4. The electrode material for a secondary battery according to claim 1 or 2, which is used for a negative electrode.

5. Electrical conductivity is 10 -6 S.C.M. -1 The electrode material for a secondary battery according to claim 1 .

6. The at least one cation is Li + , Na + , Mg 2+ , Ca 2+ , or Al 3+ The electrode material for a secondary battery according to claim 1 ,

7. The at least one anion is TFSI - , P.F. 6 - , ClO 4 - , F - , or Cl - The electrode material for a secondary battery according to claim 1 ,

8. The electrode material for a secondary battery according to any one of claims 1 to 7, wherein the metal-organic framework has at least one 3d transition element as a metal of a complex moiety.

9. 9. The electrode material for a secondary battery according to claim 1, wherein the metal-organic framework has a ligand containing at least one element selected from nitrogen, boron, oxygen, fluorine, and sulfur.

10. The electrode material for a secondary battery according to claim 1 , further comprising an auxiliary electrochemical agent and a binder.

11. A secondary battery having a positive electrode, a negative electrode, and an electrolyte, the positive electrode and negative electrode being made of an electrode material for a secondary battery, the secondary battery electrode material comprises a multi-layer metal-organic framework and is capable of electrochemically intercalating both at least one type of cation and at least one type of anion; the metal-organic framework includes a metal portion composed of at least one type of metal and an organic portion including a ligand coordinated to the at least one type of metal, and has a periodic structure in which the metal portion and the organic portion are periodically repeated due to a coordination structure between the metal portion and the organic portion; the full width at half maximum of the X-ray diffraction peak from the (100) plane of the multilayer metal-organic framework measured using CuKα radiation is 1.0° (2θ) or less; The above secondary battery, wherein the electrolytic solution is an organic electrolytic solution.

12. A secondary battery having a negative electrode, a positive electrode, and an electrolyte, the negative electrode and the positive electrode being made of an electrode material for a secondary battery, the secondary battery electrode material comprises a multi-layer metal-organic framework and is capable of electrochemically intercalating both at least one type of cation and at least one type of anion; the metal-organic framework includes a metal portion composed of at least one type of metal and an organic portion including a ligand coordinated to the at least one type of metal, and has a periodic structure in which the metal portion and the organic portion are periodically repeated due to a coordination structure between the metal portion and the organic portion; the full width at half maximum of the X-ray diffraction peak from the (100) plane of the multilayer metal-organic framework measured using CuKα radiation is 1.0° (2θ) or less; The above secondary battery, wherein the electrolytic solution is an organic electrolytic solution.

13. 13. The secondary battery according to claim 11 or 12, wherein the at least one type of cation and the at least one type of anion together function as charge carriers.

14. An electric / electronic device or a transport machine comprising the secondary battery according to any one of claims 11 to 13.

Citation Information

Patent Citations

  • Fluoride ion electrochemical cell

    JP2013145758A

  • Secondary battery, and method for manufacturing secondary battery

    JP2016103407A

  • High-performance organic electrodes for secondary batteries

    JP2017168433A

  • Use of a polymer network as a cathode material for rechargeable batteries

    WO2013107798A1